1974
DOI: 10.1111/j.1570-7458.1974.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Stimuli Affecting Oviposition Behavior of the Eastern Spruce Budworm

Abstract: The host selection of the female spruce budworm Choristoneura fumiferana (Clem.), Tortricidae, for oviposition is influenced both by the shape and the composition of the substrate. Needle extracts were bioassayed using artificial twigs. The active compounds are soluble in organic solvents and steam distillable. Synthetic D‐α and L‐β pinene occurring naturally in the extracts proved to be oviposition stimulants. The optical isomer L‐α pinene did not show any activity. Ablation experiments led to the conclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
4

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 41 publications
1
43
4
Order By: Relevance
“…In the literature (Städler 1974, Chen et al 2002, Grant et al 2007), α-pinene has been reported as budworm oviposition stimulant, but our results showed that this monoterpene, at concentrations found in the foliage, proved toxic to sixth-instar larvae, incurring 20% mortality. To reduce the toxic effect of α-pinene, spruce budworm decreases the digestibility D (Tab.…”
Section: Discussioncontrasting
confidence: 55%
“…In the literature (Städler 1974, Chen et al 2002, Grant et al 2007), α-pinene has been reported as budworm oviposition stimulant, but our results showed that this monoterpene, at concentrations found in the foliage, proved toxic to sixth-instar larvae, incurring 20% mortality. To reduce the toxic effect of α-pinene, spruce budworm decreases the digestibility D (Tab.…”
Section: Discussioncontrasting
confidence: 55%
“…moths to their host trees. 9 After dispersal of many such forest insects, the process of finding a host tree is critical for their survival. It is conceivable that increased levels of attractive terpenes could contribute towards the success of this process.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of a host for ovlposltlon by many herbivorous insects is also largely due to the presence or absence of specific plant chemicals (Stadler 1974, Renwlck 1989). …”
Section: Host Selection Behavior Selection Behavior Of Herbivoresmentioning
confidence: 99%
“…In general, both olfactory and contact chemoreceptors are Involved in oviposition host selection behavior. Chemoreceptors for ovipositional cues may be located on the antennae, tarsi, maxillary and labial palps, and the ovipositor (Stadler 1974, Renwick 1989. Actual sampling of the leaf chemistry may involve such behaviors as drumming with the foretarsl, leaf scratching with the forelegs, examining with the palpi, or walking on the leaf surface , Renwlck 1989.…”
Section: Host Selection Behavior Selection Behavior Of Herbivoresmentioning
confidence: 99%
See 1 more Smart Citation